Laminated body

By using a laminated body with Young's modulus of 0.01 to 10 GPa in the manufacturing process of the semiconductor device, the problem of insufficient transfer of the film to the adherend is solved, and sufficient bonding between the adherend and the lead frame is achieved, and transferability and bonding strength are improved.

CN113861540BActive Publication Date: 2025-05-02NITTO DENKO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202110709476.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-29
Filing Date
2021-06-25
Publication Date
2025-05-02
Estimated Expiration
2041-06-25

AI Technical Summary

Technical Problem

In the prior art, the film cannot be fully transferred to the adherent object, resulting in the failure to fully bond the adherent object to the lead frame or the like.

Method used

A laminate having a specific Young's modulus is used, which includes a substrate sheet and a metal-containing particle layer laminated on the substrate sheet. The Young's modulus of the contact surface was measured by the nano-indentation method to ensure that the metal-containing particle layer can be fully transferred to the adherent.

Benefits of technology

Full bonding between the adhered object and the lead frame, etc. is achieved, and transferability and bonding strength are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113861540B_ABST
    Figure CN113861540B_ABST
Patent Text Reader

Abstract

The present invention provides a laminate, which comprises a substrate sheet and a metal particle-containing layer laminated on the substrate sheet and containing metal particles. The substrate sheet has a contact surface in contact with the metal particle-containing layer. The Young's modulus of the substrate sheet at 23°C obtained by measuring the contact surface by nanoindentation is 0.01 to 10 GPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate. Background Art

[0002] Conventionally, in the manufacture of semiconductor devices, a paste composition containing metal particles is used to bond a semiconductor chip (hereinafter also referred to as a "chip") to a lead frame or the like (for example, Patent Documents 1 and 2).

[0003] There is also known a method of forming a film from the paste composition, transferring a part of the film to a chip, and bonding the chip to a lead frame or the like via the film (for example, Patent Document 3).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-039580

[0007] Patent Document 2: Japanese Patent Application Publication No. 2014-111800

[0008] Patent Document 3: Japanese Patent Application No. 2014-503936 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] However, the film may not be sufficiently transferred to an adherend (a chip or the like), and the adherend and a lead frame or the like may not be sufficiently bonded to each other.

[0011] Therefore, the present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a laminate having excellent transferability.

[0012] Solutions for solving problems

[0013] The laminate of the present invention comprises a base sheet and a metal particle-containing layer laminated on the base sheet and containing metal particles.

[0014] The substrate sheet has a contact surface in contact with the metal particle-containing layer.

[0015] The Young's modulus of the base sheet at 23° C. obtained by measuring the contact surface by a nanoindentation method is 0.01 to 10 GPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic cross-sectional view of the laminated body of this embodiment.

[0017] Figure 2 Schematic cross-sectional view showing a state where a semiconductor chip B is picked up from a dicing tape A by a suction collet C.

[0018] Figure 3 It is a schematic cross-sectional view showing the transfer process.

[0019] Figure 4 It is a schematic cross-sectional view showing the state of the picking-up process.

[0020] Figure 5 1 is a schematic cross-sectional view showing a state immediately before a semiconductor chip B with a metallic particle-containing layer 2 is pressed against a lead frame D from the metallic particle-containing layer 2 side by a suction collet C. FIG.

[0021] Figure 6 It is a schematic cross-sectional view showing the state of the sintering process.

[0022] Description of Reference Numerals

[0023] 1: laminate, 2: metal particle-containing layer, 3: substrate sheet, 3a: contact surface,

[0024] 31: resin layer,

[0025] A: Dicing tape, B: Semiconductor chip, C: Adsorption collet, D: Lead frame, E: Pressurization and heating device, F: Semiconductor device, G: Table, H: Table DETAILED DESCRIPTION

[0026] Hereinafter, one embodiment of the present invention will be described with reference to the drawings, taking as an example a case where the metal particle-containing layer of the laminated body of the present embodiment is a sinterable layer.

[0027] It should be noted that the metal particle layer of the laminated body of the present embodiment is a layer used by being bonded to an adherend by sintering.

[0028] like Figure 1 As shown, the laminated body 1 of the present embodiment includes a base sheet 3 and a metal particle-containing layer 2 which is laminated on the base sheet 3 and contains metal particles.

[0029] The base sheet 3 forms a resin layer 31 containing resin.

[0030] In addition, the base sheet 3 has a contact surface 3a in contact with the metal particle-containing layer 2. Specifically, the resin layer 31 has a contact surface 3a in contact with the metal particle-containing layer 2.

[0031] The metal particle-containing layer 2 is laminated on the base sheet 3 in a state where it can be peeled off from the base sheet 3 .

[0032] The laminate 1 of this embodiment is used by pressing a portion of the metal particle-containing layer 2 toward the base sheet 3 to cut it, and the cut portion is peeled off from the base sheet 3 and adhered to an adherend (eg, a chip).

[0033] More specifically, for the laminated body 1 of the present embodiment, the metal particle-containing layer 2 is pressed by a pressing member that presses a portion of the metal particle-containing layer 2 toward the substrate sheet 3, so that a portion of the metal particle-containing layer 2 is cut off for use, and the cut portion is peeled off from the substrate sheet 3 and adhered to a to-be-adhered object (such as a chip, etc.).

[0034] Examples of the resin contained in the resin layer 31 include polyolefin resins, polyester resins, polyurethane resins, polycarbonate resins, polyetheretherketone resins, polyimide resins, polyetherimide resins, polyamide resins, polyvinyl chloride, polyvinylidene chloride, polyphenylene sulfide resins, fluororesins, cellulose-based resins, and silicone resins.

[0035] Furthermore, the aforementioned resin may be an ionomer resin.

[0036] Examples of the polyolefin resin include low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolypropylene, polybutene, polymethylpentene, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylate copolymer, ethylene-butene copolymer, and ethylene-hexene copolymer.

[0037] Examples of the polyester resin include polyethylene terephthalate (PET), polyethylene naphthalate, and polybutylene terephthalate.

[0038] Examples of the polyamide resin include wholly aromatic polyamide (aramid) and the like.

[0039] Examples of the fluororesin include polytetrafluoroethylene (PTFE) and the like.

[0040] The resin layer 31 may be formed of a thin film.

[0041] The film may be a uniaxially stretched film or a biaxially stretched film.

[0042] The resin layer 31 may be a porous body.

[0043] It is important that the Young's modulus of the base sheet 3 at 23° C. measured on the contact surface 3 a by nanoindentation is 0.01 to 10 GPa, preferably 0.02 to 8 GPa, more preferably 0.1 to 5 GPa, and particularly preferably 0.3 to 3.4 GPa.

[0044] In other words, it is important for the base sheet 3 that the Young's modulus at 23° C. measured on the contact surface 3 a by nanoindentation is 0.01 to 10 GPa, preferably 0.02 to 8 GPa, more preferably 0.1 to 5 GPa, and particularly preferably 0.3 to 3.4 GPa.

[0045] The laminate 1 of this embodiment has the following advantages due to the aforementioned Young's modulus being less than 10 GPa: when an adherend (such as a chip, etc.) is pressed against the aforementioned metal particle-containing layer 2, force is easily applied to the entire portion of the metal particle-containing layer 2 that is in contact with the adherend, and as a result, the aforementioned metal particle-containing layer 2 can be fully transferred to the aforementioned adherend.

[0046] In addition, the laminate 1 of this embodiment has the following advantage because the Young's modulus is 0.01 GPa or more: when the adherend is pressed against the metal particle-containing layer 2, sufficient force can be easily applied in the direction of pressing the adherend, resulting in that the metal particle-containing layer 2 can be fully transferred to the adherend.

[0047] It should be noted that the Young's modulus can be obtained by the nanoindentation method of ISO14577 (instrument indentation test).

[0048] Specifically, it can be measured under the following conditions using a microhardness tester (manufactured by Shimadzu Corporation, DUH-211).

[0049] Indenter: Berkovich Indenter

[0050] Test mode: load-unload test

[0051] Test force: 0.98mN

[0052] Minimum test force: 0.002mN

[0053] Loading and unloading speed: 1.0mN / sec

[0054] Load holding time: 5.0 seconds

[0055] Unloading holding time: 5.0 seconds

[0056] With Cf-Ap correction

[0057] It should be noted that nanoindentation refers to a method for measuring the physical properties of a sample at a nanoscale. In the nanoindentation method, at least the process of pressing the indenter into the sample mounted on the stage (load application process) and the process of pulling the indenter out of the sample thereafter (unloading process) are implemented to measure the load acting on the indenter-sample in a series of processes and the relative displacement of the indenter relative to the sample. As a result, a load-displacement curve is obtained. The physical properties (hardness, elastic modulus, adhesion, etc.) of the sample measured based on the nanoscale can be obtained from the load-displacement curve.

[0058] The total thickness of the resin layer 31 is preferably 10 to 5000 μm, more preferably 20 to 4000 μm, and even more preferably 30 to 3000 μm.

[0059] The laminated body 1 of the present embodiment has an advantage of excellent handling properties because the total thickness of the resin layer 31 is 10 μm or more.

[0060] In addition, the laminated body 1 of the present embodiment has an advantage in that the material cost can be kept low because the total thickness of the resin layer 31 is 5000 μm or less.

[0061] It should be noted that in the present embodiment, the thickness of the layer can be measured using a micrometer.

[0062] The metal particle-containing layer 2 includes metal particles and a binder. In addition, the metal particle-containing layer 2 may include a plasticizer and the like.

[0063] The aforementioned binders include polymer binders and binders other than polymers (hereinafter also referred to as “low-molecular binders”).

[0064] In addition, the metal particle-containing layer 2 is a sinterable layer.

[0065] The sinterable layer is a layer that can be sintered by heating.

[0066] The aforementioned metal particles are sinterable metal particles.

[0067] The metal particles are conductive metal particles. The metal particle-containing layer 2 has one side and the other side bonded to the adherends, respectively, to electrically connect the adherends.

[0068] Examples of the metal particles include gold, silver, copper, palladium, tin, nickel, and alloys thereof.

[0069] In addition, examples of the metal particles include metal oxides, such as silver oxide, copper oxide, palladium oxide, and tin oxide.

[0070] The metal particles may be particles having a core-shell structure. Examples of the particles having a core-shell structure include particles including a core formed of copper and a shell covering the core and formed of gold, silver, or the like.

[0071] From the viewpoint that the metal particle-containing layer 2 can become a sintered layer firmly bonded to an adherend after sintering, the metal particles preferably contain at least one metal selected from the group consisting of silver, copper, silver oxide, and copper oxide.

[0072] Furthermore, from the viewpoint that the metal particle-containing layer 2 has excellent electrical conductivity and thermal conductivity after sintering, the metal particles preferably contain at least one metal selected from the group consisting of silver and copper.

[0073] In addition, from the viewpoint of oxidation resistance, the metal particles preferably include silver particles. Silver particles are difficult to oxidize even when sintered in an air atmosphere.

[0074] The metal particles are contained in the metal particle-containing layer 2 in the form of primary particles or in the form of secondary particles in which a plurality of primary particles are aggregated.

[0075] From the viewpoint of easily ensuring the flatness of the surface of the metal particle-containing layer 2, the volume-based median particle size (D50) of the metal particles is preferably 10,000 nm or less, more preferably 3,000 nm or less, further preferably 1,000 nm or less, and particularly preferably 500 nm or less.

[0076] In order to improve the dispersibility of the metal particles in the metal particle-containing layer 2, the volume-based median diameter (D50) of the metal particles is preferably 1 nm or more, more preferably 10 nm or more, and even more preferably 50 nm or more.

[0077] In addition, the volume-based median diameter (D50) of the metal particles is determined using a scanning electron microscope (SEM).

[0078] That is, the area of ​​each metal particle observed from one direction using a scanning electron microscope (SEM) was determined.

[0079] Next, the diameter and volume of each metal particle are determined assuming that each metal particle is a true sphere. When the metal particle is a secondary particle, the diameter and volume of the secondary particle are determined.

[0080] Furthermore, the volume-based particle size distribution is obtained from the data of the diameter and volume of each metal particle, and the volume-based median diameter (D50) of the metal particles is obtained from the volume-based particle size distribution.

[0081] The polymer binder is preferably a pyrolytic polymer binder.

[0082] The pyrolytic polymer binder is a binder that pyrolyzes at a sintering temperature. The pyrolytic polymer binder is an element that maintains the shape of the metal particle-containing layer 2 until sintering.

[0083] In the present embodiment, the pyrolytic polymer binder is preferably solid at room temperature (23° C.) from the viewpoint of easily maintaining the shape of the metal particle-containing layer 2. Examples of the pyrolytic polymer binder include polycarbonate resins and acrylic resins.

[0084] Examples of the polycarbonate resin include aliphatic polycarbonate and aromatic polycarbonate.

[0085] The aromatic polycarbonate contains a benzene ring between carbonate groups (-O-CO-O-) in the main chain.

[0086] The aforementioned aliphatic polycarbonate contains an aliphatic chain but no benzene ring between carbonate groups (—O—CO—O—) in the main chain.

[0087] Examples of the aliphatic polycarbonate include polyethylene carbonate and polypropylene carbonate.

[0088] Examples of the aromatic polycarbonate include polycarbonates containing a bisphenol A structure in the main chain.

[0089] The acrylic resin contains (meth)acrylate as a constituent unit.

[0090] Examples of the (meth)acrylate include (meth)acrylates having a linear or branched alkyl group having 4 to 18 carbon atoms.

[0091] Examples of the alkyl group include methyl, ethyl, propyl, isopropyl, n-butyl, tert-butyl, isobutyl, pentyl, isopentyl, hexyl, heptyl, cyclohexyl, 2-ethylhexyl, octyl, isooctyl, nonyl, isononyl, decyl, isodecyl, undecyl, lauryl, tridecyl, tetradecyl, stearyl, and octadecyl.

[0092] The acrylic resin may contain a monomer other than (meth)acrylic acid ester as a constituent unit.

[0093] Examples of the monomer other than the (meth)acrylate include a carboxyl group-containing monomer, an acid anhydride monomer, a hydroxyl group-containing monomer, a sulfonic acid group-containing monomer, and a phosphoric acid group-containing monomer.

[0094] Examples of the carboxyl group-containing monomer include acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid.

[0095] Examples of the acid anhydride monomer include maleic anhydride and itaconic anhydride.

[0096] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and 4-(hydroxymethyl)cyclohexylmethyl (meth)acrylate.

[0097] Examples of the sulfonic acid group-containing monomer include styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid.

[0098] As said phosphoric acid group-containing monomer, 2-hydroxyethyl acryloyl phosphate etc. are mentioned, for example.

[0099] It should be noted that in the present embodiment, "(meth)acrylic acid" is a concept including acrylic acid and methacrylic acid.

[0100] In addition, "(meth)acrylate" is a concept including acrylate and methacrylate.

[0101] The weight average molecular weight of the polymer binder is preferably 10,000 or more.

[0102] In addition, the weight average molecular weight means the weight average molecular weight measured by gel permeation chromatography (GPC) and calculated|required by polystyrene.

[0103] For example, the weight average molecular weight can be determined as follows: using GPC "HLC-8320GPC" manufactured by Tosoh Corporation as an apparatus, and setting a column "TSK guardcolumn H HR (S)" and the column "TSK GMH made by Tosoh Corporation HR -H(S)" and Tosoh Corporation's column "TSK GMH HR -H(S)" was used as a column, a total of 3 columns were connected in series, "TSKgel SuperH-RC" was used as a reference column, tetrahydrofuran was used as an eluent, GPC measurement was performed at a column temperature of 40°C and a flow rate of 0.5 ml / min, and calculation was performed from the obtained results to obtain the value in the form of polystyrene conversion.

[0104] The low-molecular binder preferably includes a low-boiling-point binder having a boiling point lower than the pyrolysis starting temperature of the pyrolytic polymer binder.

[0105] In addition, the low molecular binder is preferably liquid or semi-liquid at 23°C.

[0106] Furthermore, the low molecular weight binder preferably has a viscosity of 1×10 5 Pa·s or less.

[0107] It should be noted that the above viscosity can be measured using a dynamic viscoelasticity measuring device (trade name "HAAKE MARS III", manufactured by Thermo Fisher Scientific). The parallel plates were used as the jig, the gap between the plates was set to 100 μm, and the shear rate of the rotational shear was set to 1 s -1 .

[0108] Examples of the low-molecular binder include alcohols and ethers.

[0109] Examples of the alcohols include terpene alcohols.

[0110] Examples of the terpene alcohols include isobornylcyclohexanol, citronellol, geraniol, nerol, carveol, and α-terpineol.

[0111] Examples of alcohols other than terpene alcohols include pentanol, hexanol, heptanol, octanol, 1-decanol, ethylene glycol, diethylene glycol, propylene glycol, butanediol, and 2,4-diethyl-1,5-pentanediol.

[0112] Examples of the ethers include alkylene glycol alkyl ethers.

[0113] Examples of the alkylene glycol alkyl ethers include ethylene glycol butyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol isobutyl ether, diethylene glycol hexyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, triethylene glycol methyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl methyl ether, propylene glycol propyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, dipropylene glycol propyl ether, dipropylene glycol butyl ether, dipropylene glycol dimethyl ether, tripropylene glycol methyl ether, and tripropylene glycol dimethyl ether.

[0114] Examples of ethers other than the above-mentioned alkylene glycol alkyl ethers include ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, and dipropylene glycol methyl ether acetate.

[0115] From the viewpoint of stability at room temperature, the low molecular weight binder is preferably a terpene alcohol, and more preferably isobornylcyclohexanol.

[0116] The content of the metal particles in the metal particle-containing layer 2 is preferably 85 to 97% by mass, more preferably 88 to 96% by mass.

[0117] The metal particle-containing layer 2 contains 85 mass % or more of metal particles, thereby having the advantage that the electrical conductivity can be sufficiently exhibited after sintering.

[0118] Furthermore, since the metal particle-containing layer 2 contains 97 mass % or less of metal particles, there is an advantage that the shape of the metal particle-containing layer 2 can be easily maintained.

[0119] The content of the polymer binder in the metal particle-containing layer 2 is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass.

[0120] The metal particle-containing layer 2 contains 0.1 mass % or more of the polymer binder, thereby having the advantage that the shape of the metal particle-containing layer 2 can be easily maintained.

[0121] Furthermore, the metal particle-containing layer 2 contains 10 mass % or less of the polymer binder, thereby having the advantage that the residual component derived from the polymer binder after sintering can be reduced.

[0122] The content ratio of the low molecular weight binder in the metal particle-containing layer 2 is preferably 1 to 20% by mass, more preferably 2 to 15% by mass.

[0123] The metal particle-containing layer 2 contains 1 mass % or more of a low-molecular binder, thereby having an advantage of excellent transferability to an adherend.

[0124] Furthermore, the metal particle-containing layer 2 contains 20 mass % or less of the low-molecular binder, thereby having the advantage that the residual component derived from the low-molecular binder after sintering can be reduced.

[0125] The thickness of the metal particle-containing layer 2 is preferably 5 μm or more, more preferably 10 μm or more.

[0126] The thickness of the metal particle-containing layer 2 is preferably 300 μm or less, and more preferably 150 μm or less.

[0127] The laminated body 1 of the present embodiment has an advantage that the surface of the metallic particle-containing layer 2 can be flattened because the thickness of the metallic particle-containing layer 2 is 5 μm or more.

[0128] In addition, the laminated body 1 of the present embodiment has an advantage that cracking during handling can be suppressed because the thickness of the metal particle-containing layer 2 is 300 μm or less.

[0129] The shear fracture strength of the metal particle-containing layer 2 at 23° C. is preferably 2 to 40 MPa, more preferably 2 to 35 MPa, and even more preferably 2 to 32 MPa.

[0130] The laminated body 1 of the present embodiment has an advantage that the shape of the metallic particle-containing layer 2 can be easily maintained because the shear fracture strength of the metallic particle-containing layer 2 at 23° C. is 2 MPa or more.

[0131] The laminate 1 of the present embodiment has an advantage of excellent cutting properties during transfer to an adherend because the shear fracture strength of the metal particle-containing layer 2 at 23° C. is 40 MPa or less.

[0132] The shear fracture strength of the metallic particle-containing layer 2 at 100° C. is preferably 20 MPa or less, more preferably 9 MPa or less, and even more preferably 7 MPa or less.

[0133] The laminate 1 of the present embodiment has an advantage of excellent cutting properties during transfer to an adherend because the shear fracture strength of the metal particle-containing layer 2 at 100° C. is 20 MPa or less.

[0134] It should be noted that the shear failure strength can be obtained by the SAICAS method.

[0135] For example, the shear fracture strength can be determined using SAICAS (Surface And Interfacial Cutting Analysis System) which is an apparatus manufactured by DAIPLA WINTES CO., LTD.

[0136] Specifically, the shear strength is calculated when the metal particle-containing layer 2 is cut at a speed of 10 μm / sec in a direction parallel to the surface of the metal particle-containing layer 2 and at a speed of 0.5 μm / sec in a direction perpendicular to the surface of the metal particle-containing layer 2 using a cutting edge (blade width: 1 mm, front angle: 10°, back angle: 10°), and the shear strength is taken as the shear failure strength.

[0137] The shear fracture strength can be adjusted by, for example, adjusting at least one of the blending ratio of the polymer binder and the blending ratio of the low molecular binder, or adjusting the viscoelasticity of the polymer binder.

[0138] The minimum load reached by the metal particle-containing layer 2 during unloading when load-displacement is measured by nanoindentation at 23° C. is preferably 30 to 100 μN, more preferably 32 to 80 μN, and even more preferably 35 to 75 μN.

[0139] The laminate 1 of the present embodiment has an advantage that the metal particle-containing layer 2 is easily adhered to an adherend because the minimum load of the metal particle-containing layer 2 at 23° C. is 30 μN or more.

[0140] The laminate 1 of this embodiment has the advantage that the minimum load of the metallic particle-containing layer 2 at 23° C. is 100 μN or less, and thus when the metallic particle-containing layer 2 is covered with a release substrate, the release substrate can be easily released from the metallic particle-containing layer 2 when necessary.

[0141] The aforementioned nanoindentation method is a nanoindentation method of ISO14577 (instrumental indentation test).

[0142] The load-displacement measurement by the nanoindentation method can be performed using a nanoindenter (trade name: "Triboindenter", manufactured by Hysitron Corporation).

[0143] In addition, the measurement conditions in the load-displacement measurement by the nanoindentation method can be set to the following conditions.

[0144] Measurement mode: Single pressure measurement

[0145] Indenter used: Berkovich (triangular pyramid) type diamond indenter

[0146] Maximum load reached during load application (set value): 500μN

[0147] The indenter’s penetration speed during load application: 100 μN / sec

[0148] The pulling speed of the indenter during unloading: 100μN / sec

[0149] The metal particle-containing layer 2 can be formed on the base sheet 3 as follows.

[0150] First, varnish is prepared by mixing the materials of the metal particle-containing layer 2 with a solvent.

[0151] Next, the varnish is applied onto the base sheet 3 to form a coating film, and the coating film is dried (the solvent in the coating film is volatilized) to form the metal particle-containing layer 2 .

[0152] Examples of the solvent include ketones and alcohols. Examples of ketones include methyl ethyl ketone and the like. Examples of alcohols include methanol and ethanol and the like.

[0153] In the laminated body 1 of the present embodiment, it is preferred that the resin layer 31 (base sheet 3 ) contains at least one resin selected from the group consisting of polyolefin resins, polyamide resins, and fluororesins, and is a porous body.

[0154] In the laminated body 1 of the present embodiment, it is preferable that at least one resin selected from the group consisting of polyolefin resins, polyamide resins, and fluororesins is an ionomer resin.

[0155] Furthermore, in the laminated body 1 of the present embodiment, the metal particle-containing layer 2 preferably contains a pyrolytic polymer binder as the polymer binder.

[0156] In addition, the method for using the laminated body of the present embodiment is a method for using the laminated body 1, wherein the laminated body 1 includes a substrate sheet 3 and a metal particle-containing layer that is laminated on the substrate sheet 3 in a releasable state and contains metal particles, and the method for using includes:

[0157] by pressing the metal particle-containing layer 2 toward the substrate sheet 3, thereby cutting off a portion of the metal particle-containing layer 2; and

[0158] The cut metal particle-containing layer 2 is peeled off from the base sheet 3 and bonded to an adherend.

[0159] In the method of using the laminated body of the present embodiment, the base sheet 3 has a contact surface 3 a that is in contact with the metal particle-containing layer.

[0160] In the method of using the laminate of the present embodiment, the Young's modulus of the base sheet 3 at 23° C. measured by the nanoindentation method on the contact surface 3 a is 0.01 to 10 GPa.

[0161] In other words, the Young's modulus of the base sheet 3 at 23° C. obtained by measuring the contact surface 3 a by a nanoindentation method is 0.01 to 10 GPa.

[0162] In addition, the said Young's modulus can be measured by the method similar to what was demonstrated in the section of the laminated body 1 of this embodiment.

[0163] In the method of using the laminated body of the present embodiment, the metallic particle-containing layer 2 may be pressed by a pressing member that presses a part of the metallic particle-containing layer 2 toward the base sheet 3 .

[0164] In the method of using the laminated body of the present embodiment, the adherend to which the cut metal particle-containing layer 2 is to be adhered may be a chip.

[0165] In the method of using the laminate of this embodiment, it is preferred that the base sheet 3 has a single layer or multiple layers and has at least one resin layer 31, the surface of the resin layer 31 serves as the contact surface 3a, and the total thickness of the resin layer 31 is 10 to 5000 μm.

[0166] In the method of using the laminated body of the present embodiment, it is preferable that the content ratio of the metal particles in the metal particle-containing layer 2 is 85 to 97% by mass or less.

[0167] In the method for using the laminated body according to the present embodiment, it is preferred that the metal particles contain at least one metal selected from the group consisting of silver, copper, silver oxide, and copper oxide.

[0168] In the method of using the laminate of this embodiment, it is preferred that the shear strength of the metal particle-containing layer 2 at 23°C is 2 to 40 MPa, and the minimum load reached during unloading when load-displacement is measured by nanoindentation at 23°C is 30 to 100 μN.

[0169] The shear breaking strength at 23° C. and the minimum load reached during unloading when load-displacement measurement is performed by nanoindentation at 23° C. can be measured by the same method as described in the section on the laminate 1 of the present embodiment.

[0170] Next, a method for manufacturing the semiconductor device according to the present embodiment will be described.

[0171] First, a wafer is cut on a dicing tape to obtain semiconductor chips.

[0172] Then, if Figure 2 As shown, the semiconductor chip B is picked up from the dicing tape A by a suction collet C.

[0173] It should be noted that the semiconductor chip B is usually rectangular in plan view, more specifically, square in plan view. The thickness of the semiconductor chip B is, for example, 10 to 500 μm, more specifically, 20 to 400 μm. In addition, the area of ​​the semiconductor chip B in plan view is, for example, 0.01 to 1000 mm. 2 , more specifically, 0.04 to 500 mm 2 .

[0174] In addition, if Figure 3As shown, the laminate 1 is placed on the stage G in such a manner that the metal particle-containing layer 2 of the laminate 1 is on the upper side. The semiconductor chip B is pressed against the metal particle-containing layer 2 of the laminate 1 by the suction collet C, so that a part of the metal particle-containing layer 2 is transferred to the semiconductor chip B (transfer process), and the semiconductor chip B with the metal particle-containing layer 2 is obtained. The pressure at which the semiconductor chip B is pressed against the metal particle-containing layer 2 is preferably 0.01 to 10 MPa, and more preferably 0.1 to 5 MPa. In addition, the temperature of the suction collet C or the stage G when the semiconductor chip B is pressed against the metal particle-containing layer 2 is preferably 40 to 150° C., and more preferably 50 to 120° C.

[0175] Then, if Figure 4 As shown, the semiconductor chip B with the metal particle-containing layer 2 is picked up from the stacked body 1 by a suction collet C (pick-up step).

[0176] Then, if Figure 5 As shown, the lead frame D is placed on the stage H. The semiconductor chip B with the metal particle layer 2 is pressed against the lead frame D from the side of the metal particle layer 2 by the suction collet C, and the semiconductor chip B is crimped to the lead frame D via the metal particle layer 2. The pressure for pressing the semiconductor chip B with the metal particle layer 2 against the lead frame D from the side of the metal particle layer 2 is preferably 0.01 to 10 MPa, more preferably 0.1 to 5 MPa. In addition, the temperature of the suction collet C or the stage H when pressing the semiconductor chip B with the metal particle layer 2 against the lead frame D from the side of the metal particle layer 2 is preferably 40 to 150° C., more preferably 50 to 120° C.

[0177] It should be noted that the thickness of the lead frame D is, for example, 10 to 2000 μm, and more specifically, 400 to 1500 μm.

[0178] Then, if Figure 6 As shown, the metal particle containing layer 2 is pressurized and heated by a pressurizing and heating device E, thereby sintering the metal particles in the metal particle containing layer 2 (sintering step), and a semiconductor device F is obtained.

[0179] It should be noted that after the sintering process, the bonding wire can be bonded to a desired position.

[0180] It should be noted that the laminate of the present invention is not limited to the above-mentioned embodiment. In addition, the laminate of the present invention is not limited by the above-mentioned effects. Furthermore, the laminate of the present invention can be variously modified within the scope of the gist of the present invention.

[0181] For example, in the laminated body of the present embodiment, the metal particle-containing layer is a sinterable layer, but in the laminated body of the present invention, the metal particle-containing layer may be a die-bonding film.

[0182] In the laminate of the present embodiment, the base sheet is the resin layer 31. However, in the present invention, the base sheet may have a single layer or multiple layers. In addition, the base sheet may have two or more resin layers.

[0183] When the base sheet has two or more resin layers, the total thickness of the resin layers refers to a value obtained by summing the thicknesses of the respective resin layers.

[0184] Matters disclosed in this specification include the following matters. (1)

[0186] A laminated body comprising a substrate sheet and a metal particle-containing layer laminated on the substrate sheet and containing metal particles.

[0187] The substrate sheet has a contact surface in contact with the metal particle-containing layer.

[0188] The Young's modulus of the substrate sheet at 23° C. measured by nanoindentation on the contact surface was 0.01 to 10 GPa.

[0189] The base sheet has appropriate cushioning properties due to the Young's modulus being 0.01 to 10 GPa.

[0190] As a result, when an adherend is pressed against the metallic particle-containing layer, a portion of the metallic particle-containing layer can be sufficiently transferred to the adherend due to the appropriate cushioning properties of the base sheet.

[0191] Therefore, the laminated body has excellent transferability. (2)

[0193] The laminate according to (1) above, wherein the substrate sheet has a single layer or multiple layers and comprises at least one resin layer.

[0194] The surface of the resin layer serves as the contact surface, and the thickness of the resin layer is 10 to 5000 μm.

[0195] According to the above configuration, it is possible to obtain advantages such as excellent handling properties and low material costs. (3)

[0197] The laminate according to (1) or (2), wherein the metal particle-containing layer is laminated on the substrate sheet in a state where the metal particle-containing layer can be peeled off from the substrate sheet.

[0198] A part of the metal particle-containing layer is pressed toward the base sheet to be cut, and the cut part is peeled off from the base sheet and adhered to an adherend for use. (4)

[0200] The laminated body according to any one of (1) to (3) above, wherein the content of the metal particles in the metal particle-containing layer is 85 to 97% by mass.

[0201] According to the above configuration, the advantages are that the electrical conductivity can be sufficiently exhibited after sintering and the shape of the metal particle-containing layer can be easily maintained. (5)

[0203] The laminate according to any one of (1) to (4) above, wherein the metal particles contain at least one metal selected from the group consisting of silver, copper, silver oxide, and copper oxide.

[0204] According to the above configuration, the metal particle-containing layer can be a sintered layer that is firmly bonded to an adherend after sintering. (6)

[0206] The laminate according to any one of (1) to (5) above, wherein the shear strength of the metal particle-containing layer at 23°C is 2 to 40 MPa, and the minimum load reached during unloading when load-displacement measurement is performed by nanoindentation at 23°C is 30 to 100 μN.

[0207] According to the above configuration, since the shear fracture strength at 23° C. is 2 to 40 MPa, the following advantages can be obtained: the shape of the metal particle-containing layer can be easily maintained, and the cutting property is excellent during transfer to an adherend.

[0208] In addition, since the minimum load reached during the unloading process when the load-displacement measurement is performed by the nanoindentation method at 23°C is 30 to 100 μN, the following advantages can be obtained: the aforementioned metal particle-containing layer is easily adhered to the adherend, and when the aforementioned metal particle-containing layer is covered with a peeling substrate, the peeling substrate can be easily peeled off from the aforementioned metal particle-containing layer when necessary.

[0209] Example

[0210] Next, the present invention will be specifically described with reference to Examples and Comparative Examples.

[0211] It should be noted that the following examples are used to further illustrate the present invention in detail but do not limit the scope of the present invention.

[0212] (Example 1)

[0213] The following materials were mixed at the following blending ratio for 3 minutes using a mixer (trade name "HM-500", manufactured by KEYENCE CORPORATION) in a stirring mode of the mixer to prepare a varnish.

[0214] Silver particles as metal particles: 59.76 parts by mass

[0215] Polycarbonate resin (trade name "QPAC40", weight average molecular weight: 150,000, solid at room temperature, manufactured by Empower Materials) as a polymer binder (pyrolytic polymer binder): 0.87 parts by mass

[0216] Isobornylcyclohexanol (trade name "Tersolve MTPH", liquid at room temperature, manufactured by Nippon Terpene Chemicals, Inc.) as a low molecular binder (low boiling point binder): 0.87 parts by mass

[0217] Methyl ethyl ketone as solvent: 35.91 parts by mass

[0218] The silver particles used were silver particles containing first silver particles (volume-based median diameter (D50): 60 nm, manufactured by DOWA ELECTRONICS CO., LTD.) and second silver particles (volume-based median diameter (D50): 1100 nm, manufactured by Mitsui Mining & Smelting Co., Ltd.) at a mass ratio of 9:1.

[0219] Then, the obtained varnish was applied to a porous polyethylene sheet (porous PE sheet) (thickness: 300 μm) as a substrate sheet and dried to form a metal particle-containing layer with a thickness of 54 μm to obtain a laminate. The drying temperature was set to 110° C. and the drying time was set to 3 minutes. The metal particle content in the metal particle-containing layer was 95% by mass.

[0220] (Example 2)

[0221] A laminate was obtained in the same manner as in Example 1 except that a polytetrafluoroethylene sheet (PTFE sheet) (thickness: 300 μm) was used as the base sheet instead of the porous PE sheet.

[0222] (Example 3)

[0223] A laminate was obtained in the same manner as in Example 1 except that a sheet (thickness: 250 μm) obtained by laminating two polyethylene films (PE films) (thickness: 125 μm) was used as the base sheet instead of the porous PE sheet.

[0224] (Example 4)

[0225] A laminate was obtained in the same manner as in Example 1 except that a sheet (thickness: 300 μm) obtained by laminating three polyethylene terephthalate films (PET films) (thickness: 100 μm) was used as the base sheet instead of the porous PE sheet.

[0226] (Comparative Example 1)

[0227] A laminate was obtained in the same manner as in Example 1 except that a pressure-sensitive adhesive sheet (thickness: 230 μm) formed by laminating a pressure-sensitive adhesive layer (thickness: 20 μm) and a PE film (thickness: 210 μm) was used instead of the porous PE sheet as the substrate sheet and a varnish was applied on the pressure-sensitive adhesive layer.

[0228] (Comparative Example 2)

[0229] A laminate was obtained in the same manner as in Example 1 except that a glass epoxy sheet (thickness: 350 μm) was used as the substrate sheet instead of the porous PE sheet.

[0230] (Comparative Example 3)

[0231] A laminate was obtained in the same manner as in Example 1 except that a SUS sheet (thickness: 300 μm) was used as the base sheet instead of the porous PE sheet.

[0232] <Young's modulus>

[0233] Before applying the varnish on the substrate sheet, the Young's modulus of the substrate sheet at 23° C. was measured on the surface to be applied with the varnish (the surface to be in contact with the metal particle-containing layer after the laminate is produced).

[0234] The Young's modulus is measured by the above-mentioned method.

[0235] <Evaluation test of transferability>

[0236] The transferability evaluation test was conducted using FC3000W manufactured by TORAY ENGINEERING Co., Ltd.

[0237] First, a Si mirror chip (5 mm in length, 5 mm in width, 200 μm in thickness) with one side entirely silver-plated was pressed against the metal particle-containing layer side of the laminate of the embodiment and the comparative example using a collet heated at 90°C, thereby applying a load of 50 N for 5 seconds.

[0238] Next, the Si mirror chip was peeled off from the laminated body using a collet at a speed of 0.3 mm / sec to obtain a sample.

[0239] Then, the sample is measured using VR-3000G2 for the entire area R1 of the aforementioned side and the area R2 on which the metal particle layer is transferred to the aforementioned side, and the ratio of the aforementioned area R2 to the aforementioned area R1 (R2 / R1) is calculated, and the value of this ratio expressed as a percentage is taken as the transfer rate.

[0240] Specifically, in the measurement using VR-3000G2, first, the sample is placed on the stage so that the surface on which the metal particle-containing layer is transferred is on the upper side, and the sample is photographed with a low-magnification camera at a magnification of 25 times. Then, the area A1 of the portion protruding from the stage by more than half the thickness of the Si mirror chip (more than 100 μm from the stage) is measured, and this area A1 is set as the aforementioned area R1. In addition, the area A2 of the portion protruding from the stage by more than the sum of "the thickness of the Si mirror chip" and "half the thickness of the metal particle-containing layer" (more than 154 μm from the stage) is measured, and this area A2 is set as the aforementioned area R2.

[0241] The results are shown in the following Table 1. The transfer rates shown in the following Table 1 are values ​​obtained by taking the arithmetic mean of three measured values.

[0242]

Table 1

[0243] Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Comparative Example 2 Comparative Example 3 Young's modulus of substrate sheet (GPa) 0.0001 0.3 0.5 0.9 3.4 21 190 Thickness of substrate sheet (μm) 230 300 300 250 300 350 300 Transfer rate (%) 23.1 96.9 99.5 95.2 99.8 79.6 84.7

[0244] As shown in Table 1, the laminated body of the example had a higher transfer rate than the laminated body of the comparative example.

[0245] Therefore, according to the present invention, a laminate having excellent transferability can be provided.

Claims

1. A laminate comprising a substrate sheet and a metal particle-containing layer laminated on the substrate sheet and containing metal particles and a binder, The content ratio of the metal particles in the metal particle-containing layer is 85 to 97% by mass. The substrate sheet has a contact surface in contact with the metal particle-containing layer, The Young's modulus of the substrate sheet at 23° C. measured by nanoindentation on the contact surface is 0.01 to 10 GPa. The metal particle-containing layer is laminated on the substrate sheet in a state where it can be peeled off from the substrate sheet. The metal particle-containing layer is used by pressing a portion of the metal particle-containing layer toward the base sheet to be cut off, and the cut off portion is peeled off from the base sheet and connected to an adherend.

2. The laminate according to claim 1, wherein The substrate sheet has a single layer or multiple layers and has at least one resin layer. The surface of the resin layer serves as the contact surface, and the total thickness of the resin layer is 10 to 5000 μm.

3. The laminate according to claim 1 or 2, wherein: The metal particles include at least one metal selected from the group consisting of silver, copper, silver oxide, and copper oxide.

4. The laminate according to claim 1 or 2, wherein: The shear failure strength of the metal particle-containing layer at 23° C. is 2 to 40 MPa, and the minimum load reached during unloading when load-displacement measurement is performed by nanoindentation at 23° C. is 30 to 100 μN.

Citation Information

Patent Citations

  • Heat bonding material, heat bonding sheet body and heat bonding molding body

    JP2013039580A

  • Pasty metal particulate composition, method for manufacturing solid metal or solid metal alloy, method for joining metallic members, method for manufacturing print wire board, and method for manufacturing bump for connecting electric circuits

    JP2014111800A

  • Sintered material and mounting method using the same

    JP2014503936A

  • Multilayer film

    EP3476592A1

  • Film-shaped firing material and support-sheet-equipped film-shaped firing material

    EP3667707A1